2021
DOI: 10.1039/d1nj01038g
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosyl linkage photoisomerization in heteroleptic fluoride ruthenium complexes derived from labile nitrate precursors

Abstract: Four complexes with trans-ON-Ru-F coordinate were synthesized from the corresponding nitrate precursors. The treatment of fac-[RuNO(NH3)2(NO3)3] with hydrofluoric acid results in the substitution of the labile nitrate ligands by H2O...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…16,17 As a result, for the ruthenium nitrosyls [RuNOL 4 X] 2+ (L = NH 3 , Py), the highest thermal stability of MS1 and MS2 isomers was observed for the complexes with the trans NO–Ru–F coordinate. 2,17,18 A similar dependence was also found as a function of the formal charge of ruthenium, and the increase of the charge from −2 to +3 results in a regular increase in the thermal stability of MS1. 19 The quantum yield of NO release in solutions is mostly determined by the nature of the cis -to-NO ligands, since the presence of antennas for efficient light absorption results in the increase of the quantum yield.…”
Section: Introductionsupporting
confidence: 66%
“…16,17 As a result, for the ruthenium nitrosyls [RuNOL 4 X] 2+ (L = NH 3 , Py), the highest thermal stability of MS1 and MS2 isomers was observed for the complexes with the trans NO–Ru–F coordinate. 2,17,18 A similar dependence was also found as a function of the formal charge of ruthenium, and the increase of the charge from −2 to +3 results in a regular increase in the thermal stability of MS1. 19 The quantum yield of NO release in solutions is mostly determined by the nature of the cis -to-NO ligands, since the presence of antennas for efficient light absorption results in the increase of the quantum yield.…”
Section: Introductionsupporting
confidence: 66%
“…In the structure of triclinic phase 2 , each SO 4 2– anion is surrounded by eight [Pt­(OH) 2 (H 2 O) 4 ] 2+ molecules, six of which are directly connected to the anion by a system of H-bonds [d­(O···O) = 2.55–3.00 Å]. Both the structures contain extremely short HOH···OH – hydrogen bonds, observed in the different coordination compounds, with O···O distances (2.42 Å for 2 ) close to the shortest known one (2.41 Å in CSD 117722). The most perceptible distinction between the structures of monoclinic and triclinic phases of the sulfate salts is the arrangement of cations.…”
Section: Resultsmentioning
confidence: 93%
“…The most common synthetic routes to ruthenium nitrosyl complexes include: (a) the use of specific starting materials, which already contain the ruthenium nitrosyl moiety, via a variety of substitution reactions (NO 2 by Cl, 27 NH 3 , 28,29 pyridines, [29][30][31][32][33] pyrazine; 34 NO 3 by H 2 O, F; 35 OH by F; 22,36,37 Cl by pyridines, [38][39][40] tetradentate Schiff bases, 41,42 tetradentate 2-hydroxybenzamidobenzene derivatives, 43 bis-phosphine monoxide ligands; 44 H 2 O by Cl, 45 SO 4 ; 46 NH 3 by Cl 46 ) or metathesis reactions of Na + to Ba 2+ , 29 Ba 2+ to NH 4 + , 29 Cl − to ClO 4 − , 47 PF 6 − , 48 in solution and in the solid state; 45,46 (b) conversion of the coordinated nitro ligand into nitrosyl in acidic media (HCl, TFA, HFP 6 , HNO 3 ) reported for ruthenium triammine complex, 45 as well as for compounds with pyridine, bipyridine, terpyridine, phenanthroline, triazine, and indazole ligands (see references in Table 1); (c) direct reaction of ruthenium pyridine, bipyridine, terpyridine, porphyrin, corrole species (see Table 1) or ruthenium azole complexes 49 with NO via substitution reactions of labile monodentate ligands, e.g., Cl, [50][51][52][53][54] H 2 O, 55,56 DMSO...…”
Section: Synthesis Of Ruthenium Complexes With Chalcogenonitrosyl (Ne...mentioning
confidence: 99%
“…In particular, a record high stability has been achieved by introducing F as a trans-to-NO ligand, and it could be shown that MS1 can be generated at room temperature with a lifetime of 120-150 s. 48,137 The increase in stability for F-based complexes was predicted by theory 139 and has been further underlined by additional studies on a series of [RuF(NH 3 ) 4 NO] 2+ complexes with different counteranions 22,36,37 as well as on RuNOF complexes mixing pyridine and ammine equatorial ligands. 35 These high stabilities open the path to combining PLI with other properties, such as nonlinear optical (NLO) response. For this purpose, a non-centrosymmetric crystal of a [RuF(NH 3 ) 4 NO] 2+ complex, [RuF (NH 3 ) 4 NO]SiF 6 , has been studied for PLI and NLO response.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%